Pseudo-adhesive laminate

JP2025042359APending Publication Date: 2025-03-27OJI HLDG CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023149320
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-27

AI Technical Summary

Benefits of technology

【0014】 本発明の擬似接着積層体は、プラスチックの使用量の削減が可能であって、剥離性、段ボール剥離性及び耐水性に優れる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025042359000001
    Figure 2025042359000001
  • Figure 2025042359000002
    Figure 2025042359000002
  • Figure 2025042359000003
    Figure 2025042359000003
Patent Text Reader

Abstract

To provide a pseudo-adhesive laminate that enables the reduction of plastic usage and exhibits excellent releasability, cardboard separability, and water resistance.SOLUTION: The present invention provides a pseudo-adhesive laminate comprising a release layer and a pseudo-adhesive layer in this order on one surface of a substrate, wherein the substrate and the pseudo-adhesive layer are peelable from each other. The release layer contains an alkyl phosphate ester having an alkyl group with a carbon number of 12 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to pseudo-adhesive laminates. [Background technology]

[0002] The pseudo-adhesive laminate is used as a delivery slip label in the case of home delivery, etc., in which a slip on which information such as the destination is printed is attached to the parcel via an adhesive, and the product is delivered to the customer based on the information during the transportation process, and the recipient stamps a receipt on the slip, and only the slip is peeled off and used as a receipt. In addition, due to the advantage that once peeled off, it is difficult to restore without leaving any trace of peeling, it is used in a wide range of applications, such as confidentiality applications in which confidential information is written on at least one of the back surface of the surface substrate or the front surface of the other surface substrate, and the confidential information can be read only after peeling off the surface substrate, and once peeled off, it cannot be restored, thereby preventing the information from being stolen.

[0003] A delivery slip label using a pseudo-adhesive laminate is used by removing the release substrate and attaching it to a parcel by the adhesive layer exposed thereby. After attachment to the parcel, the support is removed by peeling when necessary. Such a delivery slip label is also called a pseudo-adhesive label, which is a label in which the substrate can be easily peeled off from the pseudo-adhesive interface after attachment to the parcel.

[0004] Conventional pseudo-adhesive labels include those in which a base paper and a shipping slip are bonded together via a pseudo-glue consisting of an adhesive and a particulate filler, and an adhesive layer and release paper are provided on the opposite side of the pseudo-glue layer of the base paper, or those in which a thermoplastic resin such as polyethylene is melt-extruded and laminated on the back of the shipping slip, and then an adhesive layer and release paper are provided.

[0005] The former requires a complicated manufacturing process, and after the slip is removed, the adhesive and the base paper remain on the parcel, which may impair the design of the parcel. The latter leaves the adhesive and thermoplastic resin layer on the parcel, but is substantially transparent and is preferable because it does not impair the information or design provided on the surface of the parcel.

[0006] In response to recent demands for reducing the environmental impact, pseudo-adhesive labels are being sought to replace the method of melt extrusion lamination of thermoplastic resins such as polyethylene, in order to reduce the amount of plastic used. Such pseudo-adhesive labels have been reported in Patent Documents 1 to 5.

[0007] Patent Document 1 reports a peelable laminate comprising a base sheet, a pseudo-release layer laminated on the base sheet, and a resin layer laminated on the pseudo-release layer, the pseudo-release layer containing a silicone acrylic resin, the resin layer containing a carboxyl group-containing resin, and the pseudo-release layer and the resin layer being peelable from each other.

[0008] Patent documents 2 to 4 report pseudo-adhesive laminates comprising a substrate and a pseudo-adhesive layer laminated on one side of the substrate, in which (1) the pseudo-adhesive layer contains a thermoplastic resin and an emulsifier having a melting point of 25°C or higher, and the content of the thermoplastic resin in the pseudo-adhesive layer is 77 to 98 mass%, (2) the pseudo-adhesive layer contains a thermoplastic resin and an emulsifier having a melting point of 25°C or higher, and when the substrate is peeled off from the pseudo-adhesive laminate at room temperature, the emulsifier contained in the pseudo-adhesive layer remains on the peeled surface on the substrate side, or (3) the pseudo-adhesive layer contains a thermoplastic resin, an emulsifier having a melting point of 25°C or higher, and a release agent.

[0009] Patent Document 5 reports an adhesive-free shipping label for parcel delivery, which includes a thermal paper layer that can be printed on its surface, an adhesive layer formed on the back surface of the thermal paper layer, and a release paper layer attached to the back surface of the adhesive layer, the release layer being located between the back surface of the thermal paper layer and the surface of the adhesive layer and formed by applying a release coating liquid composed of polyethylene glycol, polyethylene, an emulsifier and water, which separates from the back surface of the thermal paper layer when the thermal paper layer is removed and remains on the surface of the adhesive layer, and the portion remaining on the surface of the adhesive layer does not exhibit adhesiveness. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2020-163840 A [Patent Document 2] JP 2019-147316 A [Patent Document 3] JP 2019-147317 A [Patent Document 4] JP 2019-147898 A [Patent Document 5] JP 2016-175410 A Summary of the Invention [Problem to be solved by the invention]

[0011] The main object of the present invention is to provide a pseudo-adhesive laminate that can reduce the amount of plastic used and has excellent releasability, cardboard releasability and water resistance. [Means for solving the problem]

[0012] The present inventors have intensively studied the above-mentioned conventional techniques and have come to solve the above-mentioned problems. That is, the present invention relates to the following pseudo-adhesive laminate.

[0013] Item 1: A pseudo-adhesive laminate having a release layer and a pseudo-adhesive layer, in that order, on one side of a support, in which the support and the pseudo-adhesive layer are peelable, characterized in that the release layer contains an alkyl phosphate ester having an alkyl group having 12 or more carbon atoms. Item 2: The pseudo-adhesive laminate according to item 1, wherein the alkyl phosphate ester is a stearyl phosphate ester. Item 3: The pseudo-adhesive layer contains polyvinyl alcohol and / or modified polyvinyl alcohol in an amount of 20% by mass or more based on the total solid content, and the coating amount of the pseudo-adhesive layer after drying is 2 to 8 g / m 2 Item 3. The pseudo-adhesive laminate according to item 1 or 2, Item 4: The pseudo-adhesive laminate according to item 3, wherein either or both of the release layer and the pseudo-adhesive layer contain a crosslinking agent. Item 5: The pseudo-adhesive laminate according to any one of Items 1 to 4, further comprising an adhesive layer and a release substrate in this order on the pseudo-adhesive layer opposite to the release layer. Effect of the Invention

[0014] The pseudo-adhesive laminate of the present invention makes it possible to reduce the amount of plastic used, and has excellent releasability, cardboard releasability and water resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] In this specification, the expression "comprise" includes the concepts of "comprise", "consist essentially of" and "consist only of".

[0016] In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits.

[0017] The latex in the present invention includes a gel or a dried film state formed by drying a dispersion medium.

[0018] As used herein, "pseudo-adhesion" means that two layers (e.g., a support and a pseudo-adhesive layer) are adhered together under normal use conditions, but the two layers can be peeled off by pulling them by hand, etc., and then cannot be re-adhered even if they are placed on top of each other and pressed against each other.

[0019] The present invention is a pseudo-adhesive laminate having a release layer and a pseudo-adhesive layer, in that order, on one side of a support, such that the support and the pseudo-adhesive layer are peelable, and is characterized in that the release layer contains an alkyl phosphate ester having an alkyl group having 12 or more carbon atoms.

[0020] [Support] The support in the present invention is not particularly limited in type, shape, size, etc., and can be appropriately selected from, for example, high-quality paper (acid paper, neutral paper), medium-quality paper, coated paper, art paper, cast-coated paper, glassine paper, resin-laminated paper, polyolefin-based synthetic paper, synthetic fiber paper, nonwoven fabric, synthetic resin film, etc., as well as various transparent supports, etc. The thickness of the support is not particularly limited, and is usually about 20 to 200 μm.

[0021] If necessary, the support may be provided with functions such as thermal recording paper, inkjet recording paper, carbonless paper, electrostatic recording paper, xeography paper, etc., printability, concealment, etc. In the following, an embodiment in which the support is provided with the function of thermal recording paper will be described as one example.

[0022] [Thermal recording layer] When the sheet is to function as a thermal recording paper, it is provided with at least a thermal recording layer containing a leuco dye and a color developer on a support.

[0023] (Leuco dye) The heat-sensitive recording layer may contain various known colorless or light-colored leuco dyes, specific examples of which are given below.

[0024] Specific examples of leuco dyes include blue-coloring dyes such as 3,3-bis(p-dimethylaminophenyl)-6-dimethylaminophthalide, 3-(4-diethylamino-2-methylphenyl)-3-(4-dimethylaminophenyl)-6-dimethylaminophthalide, and fluoran; green dyes such as 3-(N-ethyl-Np-tolyl)amino-7-N-methylanilinofluoran, 3-diethylamino-7-anilinofluoran, 3-diethylamino-7-dibenzylaminofluoran, and rhodamine B-anilinolactam; Color-forming dyes, such as 3,6-bis(diethylamino)fluoran-γ-anilinolactam, 3-cyclohexylamino-6-chlorofluoran, 3-diethylamino-6-methyl-7-chlorofluoran, and 3-diethylamino-7-chlorofluoran, red color-forming dyes such as 3-(N-ethyl-N-isoamyl)amino-6-methyl-7-anilinofluoran, 3-(N-methyl-N-cyclohexyl)amino-6-methyl-7-anilinofluoran, 3-diethyl ... -Di(n-butyl)amino-6-methyl-7-anilinofluoran, 3-di(n-pentyl)amino-6-methyl-7-anilinofluoran, 3-(N-ethyl-N-isoamylamino)-6-methyl-7-anilinofluoran, 3-diethylamino-7-(m-trifluoromethylanilino)fluoran, 3-(N-isoamyl-N-ethylamino)-7-(o-chloroanilino)fluoran, 3-(N-ethyl-N-2-tetrahydrofurfurylamino)-6-methyl-7-anilinofluoran, 3- (Nn-hexyl-N-ethylamino)-6-methyl-7-anilinofluoran, 3-[N-(3-ethoxypropyl)-N-ethylamino]-6-methyl-7-anilinofluoran, 3-[N-(3-ethoxypropyl)-N-methylamino]-6-methyl-7-anilinofluoran, 3-diethylamino-7-(2-chloroanilino)fluoran, 3-di(n-butylamino)-7-(2-chloroanilino)fluoran, 4,4'-bis-dimethylaminobenzhydrin benzyl ether, N-2,4,5-Trichlorophenylleucoauramine, 3-diethylamino-7-butylaminofluoran, 3-ethyl-tolylamino-6-methyl-7-anilinofluoran, 3-cyclohexyl-methylamino-6-methyl-7-anilinofluoran, 3-diethylamino-6-chloro-7-(β-ethoxyethyl)aminofluoran, 3-diethylamino-6-chloro-7-(γ-chloropropyl)aminofluoran, 3-diethylamino-6-methyl-7-anilinofluoran, 3-(N-isopropyl)aminofluoran, Soamyl-N-ethylamino)-6-methyl-7-anilinofluoran, 3-dibutylamino-7-chloroanilinofluoran, 3-diethylamino-7-(o-chlorophenylamino)fluoran, 3-(N-ethyl-p-toluidino)-6-methyl-7-anilinofluoran, 3-(N-ethyl-p-toluidino)-6-methyl-7-(p-toluidino)fluoran, 3-(N-ethyl-N-tetrahydrofurfurylamino)-6-methyl-7-anilinofluoran, 3-diethylamino -6-chloro-7-anilinofluoran, 3-dimethylamino-6-methyl-7-anilinofluoran, 3-pyrrolidino-6-methyl-7-anilinofluoran, 3-piperidino-6-methyl-7-anilinofluoran, 2,2-bis{4-[6'-(N-cyclohexyl-N-methylamino)-3'-methylspiro[phthalido-3,9'-xanthene]-2'-ylamino]phenyl}propane, 3-diethylamino-7-(3'-trifluoromethylphenyl)aminofluoran, and other black pigments. Color dyes, 3,3-bis[1-(4-methoxyphenyl)-1-(4-dimethylaminophenyl)ethylene-2-yl]-4,5,6,7-tetrachlorophthalide, 3,3-bis[1-(4-methoxyphenyl)-1-(4-pyrrolidinophenyl)ethylene-2-yl]-4,5,6,7-tetrachlorophthalide, 3-p-(p-dimethylaminoanilino)anilino-6-methyl-7-chlorofluoran, 3-p-(p-chloroanilino)anilino-6-methyl-7-chlorofluoran, 3,Examples of the dyes include dyes having an absorption wavelength in the near infrared region, such as 6-bis(dimethylamino)fluorene-9-spiro-3'-(6'-dimethylamino)phthalide. Of course, the dyes are not limited to these, and two or more compounds can be used in combination as necessary.

[0025] The content of the leuco dye is not particularly limited, and is preferably about 3 to 30% by mass, more preferably about 5 to 25% by mass, and even more preferably about 7 to 25% by mass, based on the total solid content of the thermosensitive recording layer. By making it 3% by mass or more, the color development ability can be improved and the print density can be improved. By making it 30% by mass or less, the heat resistance can be improved.

[0026] (Color developer) Specific examples of the color developer include 4-tert-butylphenol, 4-acetylphenol, 4-tert-octylphenol, 4,4'-sec-butylidenediphenol, 4-phenylphenol, 4,4'-dihydroxydiphenylmethane, 4,4'-isopropylidenediphenol, 4,4'-cyclohexylidene diphenyl, 4,4'-cyclohexylidene diphenol, 1,1-bis(4-hydroxyphenyl)-ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 4,4'-bis(p- Tolylsulfonylaminocarbonylamino)diphenylmethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 2,2'-bis[4-(4-hydroxyphenyl)phenoxy]diethyl ether, 4,4'-dihydroxydiphenyl sulfide, 4,4'-thiobis(3-methyl-6-tert-butylphenol), 4,4'-dihydroxydiphenyl sulfone, 2,4'-dihydroxydiphenyl sulfone, 2,2-bis(4-hydroxyphenyl)-4-methylpentane, 2,4'-dihydroxydiphenyl sulfone , 4-hydroxy-4'-isopropoxydiphenyl sulfone, 4-hydroxy-4'-n-propoxydiphenyl sulfone, 4-hydroxy-4'-allyloxydiphenyl sulfone, 4-hydroxy-4'-benzyloxydiphenyl sulfone, 3,3'-diallyl-4,4'-dihydroxydiphenyl sulfone, butyl bis(p-hydroxyphenyl)acetate, methyl bis(p-hydroxyphenyl)acetate, hydroquinone monobenzyl ether, bis(3-allyl-4-hydroxyphenyl)sulfone, 4-hydroxy-4'- Methyldiphenylsulfone, 4-allyloxy-4'-hydroxydiphenylsulfone, 3,4-dihydroxyphenyl-4'-methylphenylsulfone, 4-hydroxybenzophenone, dimethyl 4-hydroxyphthalate, methyl 4-hydroxybenzoate, propyl 4-hydroxybenzoate, sec-butyl 4-hydroxybenzoate, phenyl 4-hydroxybenzoate, benzyl 4-hydroxybenzoate, benzyl 4-hydroxybenzoate ester, tolyl 4-hydroxybenzoate, chlorophenyl 4-hydroxybenzoate, 4,Phenolic compounds such as 4'-dihydroxydiphenyl ether, or benzoic acid, p-chlorobenzoic acid, p-tert-butylbenzoic acid, trichlorobenzoic acid, terephthalic acid, salicylic acid, 3-tert-butylsalicylic acid, 3-isopropylsalicylic acid, 3-benzylsalicylic acid, 3-(α-methylbenzyl)salicylic acid, 3,5-di-tert-butylsalicylic acid, 4-[2-(p-methoxyphenoxy)ethyloxy]salicylic acid, 4-[3-(p-tolyl aromatic carboxylic acids such as zinc 4-[3-(p-tolylsulfonyl)propyloxy]salicylic acid, 5-[p-(2-p-methoxyphenoxyethoxy)cumyl]salicylic acid, and 4-[3-(p-tolylsulfonyl)propyloxy]salicylic acid, and these phenolic compounds and salts of aromatic carboxylic acids with polyvalent metals such as zinc, magnesium, aluminum, calcium, titanium, manganese, tin, and nickel, as well as antipyrine complexes of zinc thiocyanate, and salts of terephthalaldehyde acid and other compounds. Examples of the acidic organic compounds include organic acidic compounds having a -SO2NH- bond in the molecule, such as N-(p-toluenesulfonyl)carbamoyl acid p-cumylphenyl ester, N-(p-toluenesulfonyl)carbamoyl acid p-benzyloxyphenyl ester, N-[2-(3-phenylureido)phenyl]benzenesulfonamide, and N-(o-toluoyl)-p-toluenesulfonamide. Examples of the acidic organic compounds include organic acidic compounds having a -SO2NH- bond in the molecule, such as N-(p-toluenesulfonyl)carbamoyl acid p-cumylphenyl ester, N-(p-toluenesulfonyl)carbamoyl acid p-benzyloxyphenyl ester, N-[2-(3-phenylureido)phenyl]benzenesulfonamide, and N-(o-toluoyl)-p-toluenesulfonamide. Examples of the acidic organic compounds include organic acidic compounds having a -SO2NH- bond in the molecule, such as N-(p-toluenesulfonyl)carbamoyl acid p-cumylphenyl ester, N-[2-(3-phenylureido)phenyl]benzenesulfonamide, and N-(o-toluoyl)-p-toluenesulfonamide. Examples of the acidic inorganic compounds include activated clay, attapulgite, colloidal silica, and aluminum silicate.

[0027] Further examples include urea urethane derivatives such as 4,4'-bis[(4-methyl-3-phenoxycarbonylaminophenyl)ureido]diphenyl sulfone, 4,4'-bis[(2-methyl-5-phenoxycarbonylaminophenyl)ureido]diphenyl sulfone, and 4-(2-methyl-3-phenoxycarbonylaminophenyl)ureido-4'-(4-methyl-5-phenoxycarbonylaminophenyl)ureidodiphenyl sulfone represented by the following general formula (1), and diphenyl sulfone crosslinked compounds represented by the following general formula (2). Of course, the present invention is not limited to these, and two or more compounds can be used in combination as necessary.

[0028] [ka]

[0029] [ka] (In the formula, n represents an integer of 1 to 6.)

[0030] The content of the color developer is not particularly limited and may be adjusted according to the leuco dye used. In general, it is preferably 0.5 parts by mass or more, more preferably 0.8 parts by mass or more, even more preferably 1 part by mass or more, even more preferably 1.2 parts by mass or more, and particularly preferably 1.4 parts by mass or more, relative to 1 part by mass of the leuco dye. The content of the color developer is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 4 parts by mass or less, and particularly preferably 3.5 parts by mass or less, relative to 1 part by mass of the leuco dye. By making it 0.5 parts by mass or more, the recording performance can be improved. On the other hand, by making it 10 parts by mass or less, background fogging in a high-temperature environment can be effectively suppressed.

[0031] (Storage improver) In the present invention, the heat-sensitive recording layer can further contain a storage improver, mainly for the purpose of further improving the storage stability of the color image. Examples of such storage improvers include 1,1,3-tris(2-methyl-4-hydroxy-5-cyclohexylphenyl)butane, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,1-bis(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 4,4'-[1,4-phenylenebis(1-methylethylidene)]bisphenol, and 4,4'-[1,3-phenylenebis(1-methylethylidene)]bisphenol. At least one selected from phenol compounds such as 4-benzyloxyphenyl-4'-(2-methyl-2,3-epoxypropyloxy)phenylsulfone, epoxy compounds such as 4-(2-methyl-1,2-epoxyethyl)diphenylsulfone, and 4-(2-ethyl-1,2-epoxyethyl)diphenylsulfone, and isocyanuric acid compounds such as 1,3,5-tris(2,6-dimethylbenzyl-3-hydroxy-4-tert-butyl)isocyanuric acid can be used. Of course, the present invention is not limited to these compounds, and two or more compounds can be used in combination as necessary.

[0032] When a storage stability improver is used, the amount used should be an amount effective for improving storage stability, and is usually preferably about 1 to 30 mass %, more preferably about 5 to 20 mass %, of the total solid content of the thermosensitive recording layer.

[0033] (sensitizer) A sensitizer can also be contained in the heat-sensitive recording layer in the present invention. This can increase the recording sensitivity. Examples of sensitizers include stearic acid amide, methoxycarbonyl-N-stearic acid benzamild, N-benzoylstearic acid amide, N-eicosanoic acid amide, ethylene bisstearic acid amide, behenic acid amide, methylene bisstearic acid amide, N-methylolstearic acid amide, dibenzyl terephthalate, dimethyl terephthalate, dioctyl terephthalate, diphenyl sulfone, benzyl p-benzyloxybenzoate, 1-hydroxy-2-phenyl naphthoate, 2-naphthyl benzyl ether, m-terphenyl, p-benzyl biphenyl, di-p-chlorobenzyl ester of oxalic acid, di-p-methylbenzyl ester of oxalic acid, dibenzyl ester of oxalic acid, p-tolyl biphenyl ether, di(p-methoxyphenoxyethyl) ether, 1,2-di(3-methylphenoxy) ether, and the like. p-methylthiophenyl benzyl ether, 1,4-di(phenylthio)butane, p-acetotoluidide, p-acetophenetidide, N-acetoacetyl-p-toluidine, 1,2-diphenoxymethylbenzene, di(β-biphenylethoxy)benzene, p-di(vinyloxyethoxy)benzene, 1-isopropylphenyl-2-phenylethane, di-o-chlorobenzyl adipate, 1,2-bis(3,4-dimethylphenyl)ethane, 1,3-bis(2-naphthoxy)propane, diphenyl, benzophenone, and the like. The content of the sensitizer may be an amount effective for sensitization, and is usually preferably about 2 to 40% by mass, more preferably about 5 to 25% by mass, of the total solid content of the heat-sensitive recording layer.

[0034] Other components constituting the heat-sensitive recording layer include adhesives, and if necessary, auxiliary agents such as crosslinking agents, waxes, metal soaps, water-resistant agents, pigments, dispersants, colored dyes, and fluorescent dyes can be used.

[0035] (glue) The adhesive used in the coating liquid for the thermal recording layer may be, for example, a water-soluble adhesive or a water-dispersible adhesive. Examples of the water-soluble adhesive include modified polyvinyl alcohol such as polyvinyl alcohol, carboxy-modified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, diacetone-modified polyvinyl alcohol, and silanol-modified polyvinyl alcohol, starch and its derivatives, cellulose derivatives such as methoxycellulose, carboxymethylcellulose, hydroxyethylcellulose, hydroxypropylmethylcellulose, methylcellulose, and ethylcellulose, sodium polyacrylate, polyvinylpyrrolidone, polyamide, diisobutylene-maleic anhydride copolymer salt, styrene-acrylic acid copolymer salt, styrene-maleic anhydride copolymer salt, ethylene-maleic anhydride copolymer salt, acrylamide-acrylic acid ester copolymer, acrylamide-acrylic acid ester-methacrylic acid copolymer, polyacrylamide, sodium alginate, gelatin, casein, and gum arabic. Examples of water-dispersible adhesives include emulsions of polyvinyl acetate, polyurethane, polyacrylic acid, polyacrylic acid esters, vinyl chloride-vinyl acetate copolymers, polybutyl methacrylate, ethylene-vinyl acetate copolymers, and the like, or latexes of water-insoluble polymers such as styrene-butadiene copolymers and styrene-butadiene-acrylic copolymers. The adhesives can be used alone or in combination of two or more. The content of the adhesive can be selected from a wide range, but is generally mixed in a range of preferably about 5 to 30 mass %, more preferably about 10 to 20 mass %, of the total solid content of the thermal recording layer.

[0036] (Crosslinking agent) A crosslinking agent that hardens the adhesive of the heat-sensitive recording layer or other layers can be contained in the heat-sensitive recording layer. This can improve the water resistance of the heat-sensitive recording layer. Examples of crosslinking agents include aldehyde compounds such as glyoxal, polyamine compounds such as polyethyleneimine, epoxy compounds, polyamide resins, melamine resins, glyoxylates, dimethylol urea compounds, aziridine compounds, and blocked isocyanate compounds; inorganic compounds such as ammonium persulfate, ferric chloride, magnesium chloride, sodium tetraborate, and potassium tetraborate; boric acid, boric acid triesters, boron-based polymers, hydrazide compounds, and glyoxylates. These may be used alone or in combination of two or more. The amount of the crosslinking agent used is preferably in the range of about 1 to 10 parts by mass relative to 100 parts by mass of the total solid content of the heat-sensitive recording layer. This can improve the water resistance of the heat-sensitive recording layer.

[0037] Examples of the wax include waxes such as paraffin wax, carnauba wax, microcrystalline wax, polyolefin wax, and polyethylene wax; higher fatty acid amides such as stearic acid amide and ethylene bisstearic acid amide; higher fatty acid esters; and derivatives thereof.

[0038] Examples of the metal soap include polyvalent metal salts of higher fatty acids, such as zinc stearate, aluminum stearate, calcium stearate, and zinc oleate. If necessary, various auxiliary agents such as oil repellents, antifoaming agents, and viscosity regulators can be added to the heat-sensitive recording layer within the range that does not impair the effects of the present invention.

[0039] The thermal recording layer is generally formed on a support by dispersing a leuco dye and a color developer, and optionally a storage stability improver and a sensitizer, together or separately, in water as a dispersion medium, together with water-soluble synthetic polymer compounds such as polyacrylamide, polyvinylpyrrolidone, polyvinyl alcohol, methyl cellulose, styrene-maleic anhydride copolymer salt, and other surfactants, using various stirring and wet grinding machines such as ball mills, coball mills, attritors, and vertical and horizontal sand mills, and then dispersing the mixture so that the average particle size is 2 μm or less, and mixing it with adhesives, auxiliaries, and the like, as necessary, to prepare a coating liquid for the thermal recording layer. The coating amount of the thermal recording layer is not particularly limited, and is 1 to 12 g / m2 in terms of dry mass. 2 The preferred thickness is 2 to 10 g / m 2 More preferably, 2.5 to 8 g / m 2 More preferably, 3 to 5.5 g / m 2 The heat-sensitive recording layer can be formed in two or more layers as required, and the composition and coating amount of each layer may be the same or different.

[0040] [Undercoat layer] In the present invention, if necessary, an undercoat layer can be provided between the support and the heat-sensitive recording layer, thereby improving the recording sensitivity.

[0041] The undercoat layer preferably contains an oil-absorbing pigment having an oil absorption of 70 ml / 100 g or more, particularly about 80 to 150 ml / 100 g, and / or plastic hollow particles and / or thermally expandable particles as a pigment. The oil absorption is a value determined according to the method described in JIS K 5101.

[0042] Various oil-absorbing pigments can be used, and specific examples include inorganic pigments such as calcined kaolin, amorphous silica, precipitated calcium carbonate, and talc. The average particle size of the primary particles of these oil-absorbing pigments is preferably about 0.01 to 5 μm, and more preferably about 0.02 to 3 μm. The content of the oil-absorbing pigment can be selected from a wide range, but is generally preferably about 2 to 95 mass %, and more preferably about 5 to 90 mass %, of the total solid content of the undercoat layer.

[0043] The plastic hollow particles include those conventionally known, for example, particles whose film material is an acrylic resin, a styrene resin, a vinylidene chloride resin, or the like, and whose hollow ratio is about 50 to 99%. Here, the hollow ratio is a value calculated by the following formula (d / D)×100. In the formula, d indicates the inner diameter of the organic hollow particles, and D indicates the outer diameter of the organic hollow particles. The average particle diameter of the plastic hollow particles is preferably about 0.5 to 10 μm, and more preferably about 1 to 6 μm. The content ratio of the plastic hollow particles can be selected from a wide range, but generally, it is preferably about 2 to 90 mass %, and more preferably about 5 to 70 mass %, of the total solid content of the undercoat layer.

[0044] When an oil-absorbing inorganic pigment is used in combination with hollow plastic particles, the oil-absorbing inorganic pigment and hollow plastic particles are used within the above-mentioned content range, and the combined amount of the oil-absorbing inorganic pigment and hollow plastic particles is preferably about 5 to 90 mass %, and more preferably about 10 to 80 mass %, of the total solid content of the undercoat layer.

[0045] The undercoat layer is formed on the support by, for example, applying a coating liquid for the undercoat layer prepared by mixing an adhesive, hollow particles, pigments, auxiliaries, etc., with water as a medium, and then drying the coating liquid. The amount of the coating liquid for the undercoat layer to be applied is not particularly limited, but is preferably 2 to 20 g / m2 in terms of dry mass. 2 The preferred thickness is 2 to 12 g / m 2 degree is more preferable.

[0046] Examples of auxiliaries contained in the coating liquid for the undercoat layer include dispersants such as sodium dioctyl sulfosuccinate, sodium dodecylbenzenesulfonate, sodium lauryl alcohol sulfate, and fatty acid metal salts; waxes such as zinc stearate, calcium stearate, polyethylene wax, carnauba wax, paraffin wax, and ester wax; water-resistant agents such as hydrazide compounds, boric acid, dialdehyde starch, glyoxylates, and epoxy compounds; antifoaming agents, coloring dyes, and fluorescent dyes.

[0047] Examples of adhesives include polyvinyl alcohol and its derivatives, starch and its derivatives, cellulose derivatives such as hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, and ethyl cellulose, water-soluble polymer materials such as sodium polyacrylate, polyvinylpyrrolidone, acrylamide-acrylic acid ester copolymers, acrylamide-acrylic acid ester-methacrylic acid ester copolymers, styrene-maleic anhydride copolymers, isobutylene-maleic anhydride copolymers, casein, gelatin, and their derivatives, as well as emulsions of polyvinyl acetate, polyurethane, polyacrylic acid, polyacrylic acid esters, vinyl chloride-vinyl acetate copolymers, polybutyl methacrylate, and ethylene-vinyl acetate copolymers, or latexes of water-insoluble polymers such as styrene-butadiene copolymers and styrene-butadiene-acrylic copolymers. The content of the adhesive can be selected from a wide range, but is generally preferably about 10 to 70% by mass, more preferably about 15 to 60% by mass, of the total solid content of the undercoat layer.

[0048] [Protective layer] A protective layer may be provided on the thermal recording layer as necessary. The protective layer preferably contains mainly an adhesive. Furthermore, the protective layer preferably contains a lubricant such as polyolefin wax or zinc stearate for the purpose of preventing sticking to the thermal head, and may also contain an ultraviolet absorber and a pigment. Furthermore, by providing a glossy protective layer, the added value of the product can be increased.

[0049] The pigment contained in the protective layer is not particularly limited, and examples thereof include inorganic pigments such as amorphous silica, kaolin, clay, light calcium carbonate, heavy calcium carbonate, calcined kaolin, titanium oxide, magnesium carbonate, aluminum hydroxide, colloidal silica, and synthetic layered mica, and plastic pigments such as urea-formaldehyde resin filler.

[0050] The adhesive contained in the protective layer is not particularly limited, and a water-soluble or water-dispersible aqueous adhesive can be used. The adhesive can be appropriately selected from those that can be used in the thermal recording layer. Among these adhesives, various modified polyvinyl alcohols such as acetoacetyl-modified polyvinyl alcohol, carboxy-modified polyvinyl alcohol, and diacetone-modified polyvinyl alcohol are more preferably used.

[0051] The protective layer is formed on the thermosensitive recording layer by, for example, applying a coating liquid for the protective layer, which is prepared by mixing a pigment, an adhesive, and, if necessary, an auxiliary, etc., in water as a dispersion medium, and then drying the coating liquid. The amount of the coating liquid for the protective layer is not particularly limited, and is preferably 0.3 to 15 g / m2 in terms of dry mass. 2 The preferred range is 0.3 to 10 g / m 2 The preferred range is 0.5 to 8 g / m 2 More preferably, the thickness is 1 to 8 g / m 2 The preferred range is 1 to 5 g / m 2 The protective layer may be formed in two or more layers as required, and the composition and coating amount of each layer may be the same or different.

[0052] [Peeling layer] The pseudo-adhesive laminate of the present invention has a release layer on one side of the support. This makes it possible to peel the support from the pseudo-adhesive layer. The release layer contains an alkyl phosphate ester having an alkyl group with 12 or more carbon atoms.

[0053] By including an alkyl phosphate ester having an alkyl group having 12 or more carbon atoms, the releasability can be improved.

[0054] The alkyl phosphate ester is a compound in which the hydrogen atom of one or more of the three hydroxyl groups of phosphoric acid is replaced with an alkyl group, and among them, a monoester (monoalkyl phosphate ester), a diester (dialkyl phosphate ester), and a mixture of a monoester and a diester are preferred. The number of carbon atoms of the alkyl group of the ester portion of the alkyl phosphate ester is preferably 13 or more, more preferably 14 or more, even more preferably 15 or more, even more preferably 16 or more, particularly preferably 17 or more, and most preferably 18 or more. The alkyl phosphate ester is preferably stearyl phosphate. The alkyl group may be linear or branched.

[0055] The alkyl phosphate ester includes both free and salt forms. Examples of salts include inorganic salts, organic amine salts, and basic amino acid salts. Examples of inorganic salts include alkali metal salts such as sodium salts and potassium salts; alkaline earth metal salts such as magnesium salts and calcium salts; ammonium salts; aluminum salts; and zinc salts. Examples of organic amine salts include monoethanolamine salts, diethanolamine salts, and triethanolamine salts. Examples of basic amino acid salts include arginine salts and lysine salts.

[0056] The content of the alkyl phosphate ester is preferably about 20 to 100 mass % of the total solid content of the release layer, more preferably about 30 to 100 mass %, and even more preferably about 50 to 90 mass %. By making it 20 mass % or more, the releasability of the pseudo-adhesive interface can be improved.

[0057] As other component materials constituting the release layer, in addition to the above alkyl phosphate ester, adhesives, pigments, crosslinking agents, waxes, metal soaps, antifoaming agents, etc. may be further used as necessary.

[0058] Examples of adhesives include polyvinyl alcohol and its derivatives, starch and its derivatives, cellulose derivatives such as hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, and ethyl cellulose, water-soluble polymer materials such as sodium polyacrylate, polyvinylpyrrolidone, acrylamide-acrylic acid ester copolymers, acrylamide-acrylic acid ester-methacrylic acid ester copolymers, styrene-maleic anhydride copolymers, isobutylene-maleic anhydride copolymers, casein, gelatin, and their derivatives, as well as emulsions of polyvinyl acetate, polyurethane, polyacrylic acid, polyacrylic acid esters, vinyl chloride-vinyl acetate copolymers, polybutyl methacrylate, and ethylene-vinyl acetate copolymers, or latexes of water-insoluble polymers such as styrene-butadiene copolymers and styrene-butadiene-acrylic copolymers. The content of the adhesive can be selected from a wide range, but is generally preferably about 0 to 40% by mass, more preferably about 0 to 25% by mass, of the total solid content of the release layer.

[0059] Examples of pigments include inorganic pigments such as clay, calcined clay, diatomaceous earth, talc, kaolin, calcined kaolin, light or heavy calcium carbonate, precipitated calcium carbonate, magnesium carbonate, zinc oxide, aluminum oxide, aluminum hydroxide, magnesium hydroxide, titanium dioxide, barium sulfate, zinc sulfate, amorphous silica, amorphous calcium silicate, and colloidal silica, and organic pigments such as melamine resin, urea-formalin resin, polyethylene, nylon, styrene, acrylic, and hydrocarbons. The content of the pigment can be selected from a wide range, but is generally preferably about 0 to 60% by mass, and more preferably about 0 to 40% by mass, of the total solid content of the pseudo-adhesive layer.

[0060] A crosslinking agent that hardens the adhesive of the pseudo-adhesive layer can be contained in the release layer. This can improve the water resistance of the pseudo-adhesive layer. Examples of crosslinking agents include aldehyde compounds such as glyoxal, polyamine compounds such as polyethyleneimine, epoxy compounds, polyamide resins, melamine resins, glyoxylates, dimethylol urea compounds, aziridine compounds, and blocked isocyanate compounds; inorganic compounds such as ammonium persulfate, ferric chloride, magnesium chloride, sodium tetraborate, and potassium tetraborate; boric acid, boric acid triesters, boron-based polymers, hydrazide compounds, and glyoxylates. These may be used alone or in combination of two or more. The amount of the crosslinking agent used is preferably in the range of about 1 to 10 parts by mass relative to 100 parts by mass of the total solid content of the release layer. This can improve the water resistance of the pseudo-adhesive layer.

[0061] The release layer is formed on the support by, for example, applying a coating liquid for the release layer, which is prepared by mixing an alkyl phosphate ester, and optionally an adhesive, a pigment, a crosslinking agent, an antifoaming agent, etc., with water as a dispersion medium, and then drying the coating liquid. The amount of the coating liquid for the release layer is not particularly limited, and is 0.3 to 5 g / m in terms of dry mass. 2 The preferred range is 0.4 to 4 g / m 2 The preferred range is 0.5 to 3 g / m 2 A degree is even more preferable.

[0062] [Pseudo adhesive layer] The pseudo-adhesive laminate of the present invention has a pseudo-adhesive layer on a release layer. This allows the support and the pseudo-adhesive layer to be adhered to each other under normal use conditions, but to be peeled off when necessary. The pseudo-adhesive layer preferably contains mainly an adhesive.

[0063] Examples of adhesives include polyvinyl alcohol and its derivatives, starch and its derivatives, cellulose derivatives such as hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, and ethyl cellulose, sodium polyacrylate, polyvinylpyrrolidone, acrylic resins, acrylamide-acrylic acid ester copolymers, acrylamide-acrylic acid ester-methacrylic acid ester copolymers, styrene-maleic anhydride copolymers, isobutylene-maleic anhydride copolymers, casein, gelatin, and water-soluble polymer materials such as derivatives thereof, as well as emulsions of polyvinyl acetate, polyurethane, polyacrylic acid, polyacrylic acid esters, vinyl chloride-vinyl acetate copolymers, polybutyl methacrylate, ethylene-acrylic acid copolymers, and ethylene-vinyl acetate copolymers, or latexes of water-insoluble polymers such as styrene-butadiene copolymers and styrene-butadiene-acrylic copolymers. The content of the adhesive can be selected from a wide range, but generally, it is preferably about 40 to 90% by mass, and more preferably about 50 to 70% by mass, of the total solid content of the pseudo-adhesive layer.

[0064] Examples of the acrylic resin include those made of (meth)acrylic acid and monomer components copolymerizable with (meth)acrylic acid. Examples of the components copolymerizable with (meth)acrylic acid include alkyl acrylate resins such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and octyl (meth)acrylate, epoxy resins, silicone resins, modified alkyl acrylate resins such as the alkyl acrylate resins modified with styrene or a derivative thereof, (meth)acrylonitrile, acrylic esters, and hydroxyalkyl acrylic esters.

[0065] The adhesive is preferably polyvinyl alcohol and / or modified polyvinyl alcohol, more preferably modified polyvinyl alcohol. Examples of modified polyvinyl alcohol include acetoacetyl-modified polyvinyl alcohol, carboxy-modified polyvinyl alcohol, diacetone-modified polyvinyl alcohol, and silanol-modified polyvinyl alcohol. By containing polyvinyl alcohol and / or modified polyvinyl alcohol as the adhesive, the coating strength can be increased, and the pseudo-adhesive layer can be prevented from being partially torn at a location where adhesion is poor when the adhesive is applied to the cardboard surface, thereby improving the cardboard peelability. In addition, when the adhesive contains polyvinyl alcohol and / or modified polyvinyl alcohol, it is preferable to contain a crosslinking agent in either one or both of the peeling layer and the pseudo-adhesive layer, since this can improve water resistance. The content ratio of polyvinyl alcohol and / or modified polyvinyl alcohol is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, based on the total solid content of the pseudo-adhesive layer. The content of polyvinyl alcohol and / or modified polyvinyl alcohol is preferably 80% by mass or less, more preferably 65% ​​by mass or less, and even more preferably 50% by mass or less, based on the total solid content of the pseudo-adhesive layer. By making it 15% by mass or more, the corrugated board peelability can be improved. By making it 80% by mass or less, the drying load of the coating liquid can be suppressed, and production efficiency can be improved.

[0066] As other component materials constituting the pseudo-adhesive layer, in addition to the adhesive, pigments, crosslinking agents, waxes, antifoaming agents, etc. may be used as necessary.

[0067] Examples of pigments include inorganic pigments such as clay, calcined clay, diatomaceous earth, talc, kaolin, calcined kaolin, light or heavy calcium carbonate, precipitated calcium carbonate, magnesium carbonate, zinc oxide, aluminum oxide, aluminum hydroxide, magnesium hydroxide, titanium dioxide, barium sulfate, zinc sulfate, amorphous silica, amorphous calcium silicate, and colloidal silica, and organic pigments such as starch particles, melamine resin, urea-formalin resin, polyethylene, nylon, styrene, acrylic, and hydrocarbons. Pigments that do not impair the transparency of the pseudo-adhesive layer are preferably clay, kaolin, and colloidal silica. The content of the pigment can be selected from a wide range, but is generally preferably about 0 to 60% by mass, and more preferably about 10 to 40% by mass, of the total solid content of the release layer.

[0068] A crosslinking agent that hardens the adhesive of the pseudo-adhesive layer can be contained in the pseudo-adhesive layer. This can improve the water resistance of the pseudo-adhesive layer. Examples of crosslinking agents include aldehyde compounds such as glyoxal, polyamine compounds such as polyethyleneimine, epoxy compounds, polyamide resins, melamine resins, glyoxylates, dimethylol urea compounds, aziridine compounds, and blocked isocyanate compounds; inorganic compounds such as ammonium persulfate, ferric chloride, magnesium chloride, sodium tetraborate, and potassium tetraborate; boric acid, boric acid triesters, boron-based polymers, hydrazide compounds, and glyoxylates. These may be used alone or in combination of two or more. The amount of the crosslinking agent used is preferably in the range of about 1 to 10 parts by mass relative to 100 parts by mass of the total solid content of the pseudo-adhesive layer. This can improve the water resistance of the pseudo-adhesive layer.

[0069] The pseudo-adhesive layer is formed on the release layer by, for example, applying a coating liquid for the pseudo-adhesive layer prepared by mixing an adhesive, a pigment, a crosslinking agent, etc., as necessary, with water as a dispersion medium, and then drying the coating liquid. The amount of the coating liquid for the pseudo-adhesive layer to be applied is not particularly limited, and is 1 to 12 g / m2 in terms of dry mass. 2 The preferred thickness is 1.5 to 10 g / m 2 The preferred range is 2 to 8 g / m 2A degree is even more preferable.

[0070] [Other layers] In the present invention, it is preferable to have an adhesive layer and a release substrate in this order on the pseudo-adhesive layer on the opposite side of the release layer. This allows the pseudo-adhesive laminate to be a pseudo-adhesive label. The adhesive layer can be made into an adhesive paper by, for example, applying a coating process with an adhesive. As the release substrate, a release agent layer is formed by applying a solvent or solventless silicone resin, fluorine resin, etc. to a release paper substrate and then curing with heat, electron beam, ultraviolet light, etc., as appropriate. Examples of release paper substrates include substrates in which a filling layer is provided on base paper such as high-density paper such as glassine paper, clay-coated paper, kraft paper, or fine paper, using, for example, casein, dextrin, starch, carboxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, polyvinyl alcohol, styrene-butadiene copolymer, ethylene-vinyl chloride copolymer, methyl methacrylate-butadiene copolymer, ethylene-vinyl acetate copolymer, (meth)acrylic acid ester copolymer, or other natural or synthetic resin alone, or in combination with inorganic pigments such as kaolin, clay, calcium carbonate, calcined clay (calcined kaolin), titanium oxide, silica, or other organic pigments such as plastic pigments, or polylaminated paper in which a synthetic resin such as polyethylene is laminated on kraft paper, fine paper, glassine paper, or the like.

[0071] It is also possible to make a linerless label that does not require a release substrate by coating a release layer containing silicone on the support and coating an adhesive on the pseudo-adhesive layer. If the pseudo-adhesive layer is transparent or translucent, a printing layer can be provided on the pseudo-adhesive layer on the opposite side to the release layer or on the adhesive layer. In this case, when the support is peeled off, the printing layer becomes visible and the printed information can be confirmed.

[0072] [Pseudo-peeled laminate] The pseudo-release laminate can be produced by forming each of the layers on a support. As a method for forming each of the layers on a support, any of known coating methods such as an air knife method, a blade method, a gravure method, a roll coater method, a spray method, a dip method, a bar method, a curtain method, a slot die method, a slide die method, and an extrusion method may be used. In addition, each coating material may be applied and dried one by one to form each layer, or the same coating material may be applied in two or more layers. Furthermore, simultaneous multi-layer coating in which two or more layers are applied simultaneously may be performed. In addition, after each layer is formed or in any process after all layers are formed, a smoothing treatment can be performed using a known method such as a super calendar or a soft calendar. In addition, an adhesive layer may be formed on a release substrate first, and then the pseudo-adhesive layer and the adhesive layer are laminated together. EXAMPLES

[0073] The present invention will be described in more detail with reference to examples, but the present invention is not limited thereto. Unless otherwise specified, "parts" and "%" respectively indicate "parts by mass" and "% by mass".

[0074] Example 1 Preparation of coating solution for undercoat layer A dispersion of 58.5 parts of calcined kaolin (trade name: Ansilex 93, manufactured by BASF) and 1 part of sodium polyacrylate (trade name: Aron T-50, manufactured by Toagosei Co., Ltd., solid content concentration 40%) in 71.5 parts of water was mixed and stirred with a composition consisting of 95.2 parts of microhollow particles (trade name: Ropeike SN-1055, manufactured by Dow Chemical Co., Ltd., solid content concentration 26.5%), 21 parts of styrene-butadiene copolymer latex (trade name: L-1571, manufactured by Asahi Kasei Chemicals Co., Ltd., solid content concentration 48%), 2 parts of carboxymethylcellulose (trade name: Cellogen 7A, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 24.2 parts of a 20% solution of saturated monocarboxylic acid starch ester (trade name: Petrocoat C-8, manufactured by Nippon Starch Chemical Co., Ltd.), and 19.5 parts of water to obtain a coating liquid for an undercoat layer.

[0075] Preparation of solution A (leuco dye dispersion) A composition consisting of 100 parts of 3-di(n-butyl)amino-6-methyl-7-anilinofluoran, 50 parts of a 20% aqueous solution of sulfone-modified polyvinyl alcohol (trade name: Gohsenex L-3266, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.), 3 parts of a natural oil-based defoamer (trade name: Nopco 1407H, manufactured by San Nopco Ltd., solids concentration 15%), and 90 parts of water was ground in a sand mill until the median diameter reached 0.5 μm as measured by a laser diffraction particle size distribution analyzer SALD2200 (manufactured by Shimadzu Corporation), to obtain liquid A.

[0076] Preparation of B solution (coloring agent dispersion) A composition consisting of 100 parts of 4,4'-dihydroxydiphenyl sulfone, 40 parts of a 20% aqueous solution of carboxylic acid-modified polyvinyl alcohol (trade name: Kuraray Poval 3-86SD, manufactured by Kuraray Co., Ltd.), 3 parts of a natural oil-based defoamer (trade name: Nopco 1407H, manufactured by San Nopco Co., Ltd., solids concentration 15%), and 90 parts of water was ground in a sand mill until the median diameter reached 0.9 μm as measured by a laser diffraction particle size distribution analyzer SALD2200 (manufactured by Shimadzu Corporation), to obtain liquid B.

[0077] Preparation of coating liquid for thermal recording layer 17.6 parts of solution A, 47.3 parts of solution B, 40 parts of a 10% aqueous solution of fully saponified polyvinyl alcohol (trade name: JF-10, manufactured by Nippon Vinyl Acetate & Poval), 75 parts of a 20% aqueous solution of saturated monocarboxylic acid starch ester (trade name: Petrocoat C-8, manufactured by Nippon Starch Chemical), 25 parts of aluminum hydroxide (trade name: Hijilite H-42M, manufactured by Showa Denko), 10 parts of silica (trade name: Nipsil E-743, manufactured by Tosoh Silica), stearic acid amide (trade name: Himicron A coating liquid for a thermal recording layer was prepared by mixing and stirring a composition consisting of 32 parts of L-271 (manufactured by Chukyo Yushi Co., Ltd., solids concentration 25%), 16.7 parts of zinc stearate (trade name: Hydrin Z-8-36, manufactured by Chukyo Yushi Co., Ltd., solids concentration 36%), 6.7 parts of paraffin wax (trade name: Hydrin L-700, manufactured by Chukyo Yushi Co., Ltd., solids concentration 30%), 5 parts of a 10% aqueous solution of dioctyl sulfosuccinic acid sodium salt (trade name: SN Wet OT-70, manufactured by San Nopco Co., Ltd.), and 49 parts of water.

[0078] Preparation of coating solution for release layer A composition consisting of 42.8 parts of stearyl phosphate potassium salt (product name: U-Pol 1800, manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., solids concentration 35%), 0.9 parts of a silicone-based defoamer (product name: X-50-1003, manufactured by Shin-Etsu Chemical Co., Ltd., solids concentration 33%), and 58.3 parts of water was mixed and stirred to obtain a coating liquid for a release layer.

[0079] Preparation of coating solution for pseudo-adhesive layer A composition consisting of 62.5 parts of a 12% aqueous solution of diacetone-modified polyvinyl alcohol (trade name: DF-10, manufactured by Japan Vinyl Acetate & Poval Co., Ltd.), 18.2 parts of an acrylic resin emulsion (trade name: Polysol AM2270, manufactured by Showa Denko K.K., solids concentration 48%), 14.6 parts of a 60% dispersion of kaolin (trade name: ASP179, manufactured by BASF), 0.5 parts of a natural oil-based defoamer (trade name: Nopco 1407H, manufactured by San Nopco Ltd., solids concentration 15%), 0.5 parts of adipic acid dihydrazide (manufactured by Otsuka Chemical Co., Ltd.), and 6 parts of water was mixed and stirred to obtain a coating liquid for a pseudo-adhesive layer.

[0080] - Preparation of thermal recording medium Basis weight 63g / m 2 The coating liquid for the undercoat layer and the coating liquid for the thermal recording layer were applied on one side of the high-quality paper in an amount of 5.0 g / m2 after drying. 2 , 3.5g / m 2 After the undercoat layer and the thermosensitive recording layer were successively formed, the surface was smoothed by a supercalender to obtain a thermosensitive recording medium.

[0081] -Preparation of pseudo-adhesive laminates A coating liquid for a peeling layer and a coating liquid for a pseudo-adhesive layer were applied to the surface of the thermosensitive recording medium opposite to the surface on which the undercoat layer and the thermosensitive recording layer were formed, in a coating amount of 1.0 g / m2 after drying. 2 , 4.5g / m 2 The coating was then dried so as to form a release layer and a pseudo-adhesive layer in this order, thereby obtaining a pseudo-adhesive laminate.

[0082] - Creation of pseudo-adhesive labels An emulsion-based acrylic adhesive was applied to a release substrate so that the thickness after drying would be 18 μm, and after drying, it was attached to the pseudo-adhesive layer surface of the pseudo-adhesive laminate to produce a pseudo-adhesive label.

[0083] Example 2 A pseudo-adhesive label was obtained in the same manner as in Example 1, except that in preparing the coating liquid for the release layer in Example 1, 42.8 parts of stearyl phosphate potassium salt (trade name: U-Pol 1800, manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., solid content concentration 35%) was replaced with 30 parts of lauryl phosphate potassium salt (trade name: F-Cole 301, manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., solid content concentration 50%), and the amount of water was replaced with 71.1 parts instead of 58.3 parts.

[0084] Example 3 In the preparation of the coating liquid for the release layer in Example 1, 34 parts of stearyl phosphate potassium salt (trade name: Woopol 1800, manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., solid content concentration 35%), 0.9 parts of a silicone-based defoaming agent (trade name: X-50-1003, manufactured by Shin-Etsu Chemical Co., Ltd., solid content concentration 33%), and 58.3 parts of water were replaced with 34 parts of stearyl phosphate potassium salt (trade name: Woopol 1800, manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., solid content concentration 35%). A composition consisting of 2.3 parts of a 12% aqueous solution of fully saponified polyvinyl alcohol (trade name: JF-10, manufactured by Nippon Vinyl Acetate & Poval Co., Ltd.), 25 parts of a 12% aqueous solution of fully saponified polyvinyl alcohol (trade name: JF-10, manufactured by Nippon Vinyl Acetate & Poval Co., Ltd.), 8.3 parts of a 60% dispersion of kaolin (trade name: ASP179, manufactured by BASF Co., Ltd.), 1.2 parts of a silicone-based defoamer (trade name: X-50-1003, manufactured by Shin-Etsu Chemical Co., Ltd., solids concentration 33%), and 33.2 parts of water was used, and in the preparation of the pseudo-adhesive laminate of Example 1, the coating amount of the release layer coating liquid after drying was 1.0 g / m 2 Instead of 2.5g / m 2 A pseudo-adhesive label was obtained in the same manner as in Example 1, except that the above-mentioned was used.

[0085] Example 4 In preparing the coating liquid for the peeling layer of Example 3, the amount of 60% dispersion of kaolin (product name: ASP179, manufactured by BASF) was changed from 8.3 parts to 6.7 parts, the amount of water was changed from 33.2 parts to 33.8 parts, and 1.0 part of adipic acid dihydrazide (manufactured by Otsuka Chemical Co., Ltd.) was added; and in preparing the coating liquid for the pseudo-adhesive layer, the amount of adipic acid dihydrazide (manufactured by Otsuka Chemical Co., Ltd.) was changed from 0.5 parts to 0 parts, and the amount of water was changed from 6 parts to 4.5 parts. Except for this, a pseudo-adhesive label was obtained in the same manner as in Example 3.

[0086] Example 5 In preparing the coating liquid for the pseudo-adhesive layer of Example 3, a pseudo-adhesive label was obtained in the same manner as in Example 3, except that 62.5 parts of a 12% aqueous solution of fully saponified polyvinyl alcohol (product name: JF-10, manufactured by Nippon Vacuum Acetate & Poval) was used instead of 62.5 parts of a 12% aqueous solution of diacetone-modified polyvinyl alcohol (product name: DF-10, manufactured by Nippon Vacuum Acetate & Poval), the amount of adipic acid dihydrazide (manufactured by Otsuka Chemical Co., Ltd.) was changed from 0.5 parts to 0 parts, and the amount of water was changed from 6 parts to 4.5 parts.

[0087] Example 6 In preparing the coating liquid for the pseudo-adhesive layer in Example 3, a composition consisting of 33.9 parts of an acrylic resin emulsion (trade name: Polysol AM2270, manufactured by Showa Denko K.K., solids concentration 48%) and 28 parts of water was used instead of a composition consisting of 62.5 parts of a 12% aqueous solution of diacetone-modified polyvinyl alcohol (trade name: DF-10, manufactured by Japan Vinyl Acetate & Poval Co., Ltd.), 18.2 parts of an acrylic resin emulsion (trade name: Polysol AM2270, manufactured by Showa Denko K.K., solids concentration 48%), 0.5 parts of adipic acid dihydrazide (manufactured by Otsuka Chemical Co., Ltd.), and 6 parts of water. A pseudo-adhesive label was obtained in the same manner as in Example 3, except that a composition consisting of 33.9 parts of an acrylic resin emulsion (trade name: Polysol AM2270, manufactured by Showa Denko K.K., solids concentration 48%) and 28 parts of water was used instead of a composition consisting of 62.5 parts of a 12% aqueous solution of diacetone-modified polyvinyl alcohol (trade name: DF-10, manufactured by Japan Vinyl Acetate & Poval Co., Ltd.), 18.2 parts of an acrylic resin emulsion (trade name: Polysol AM2270, manufactured by Showa Denko K.K., solids concentration 48%) and 28 parts of water.

[0088] Example 7 A pseudo-adhesive label was obtained in the same manner as in Example 3, except that in the release layer coating liquid of Example 3, the amount of stearyl phosphate potassium salt (trade name: U-Pol 1800, manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., solids concentration 35%) was changed from 34.3 parts to 17.1 parts, the amount of 12% aqueous solution of fully saponified polyvinyl alcohol (trade name: JF-10, manufactured by Nippon Vacuum & Poval Co., Ltd.) was changed from 25 parts to 41.7 parts, the amount of 60% dispersion of kaolin (trade name: ASP179, manufactured by BASF) was changed from 8.3 parts to 15 parts, and the amount of water was changed from 33.3 parts to 6.6 parts.

[0089] Comparative Example 1 A pseudo-adhesive label was obtained in the same manner as in Example 1, except that in preparing the coating liquid for the release layer in Example 1, 42.8 parts of stearyl phosphate potassium salt (product name: Woopol 1800, manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., solid content concentration 35%) was replaced with 30 parts of hexyl phosphate potassium salt (product name: Woopol 60, manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., solid content concentration 50%), and the amount of water was replaced with 71.1 parts instead of 58.3 parts.

[0090] Comparative Example 2 A pseudo-adhesive label was obtained in the same manner as in Example 1, except that in preparing the coating liquid for the release layer in Example 1, 42.8 parts of stearyl phosphate potassium salt (product name: U-Pol 1800, manufactured by Matsumoto Yushi Seiyaku Co., Ltd., solids concentration 35%) was replaced with 15 parts of phosphate ester of styrenated phenol ethoxylate (product name: Plysurf AL, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and the amount of water was replaced with 86.1 parts instead of 58.3 parts.

[0091] Comparative Example 3 A pseudo-adhesive label was obtained in the same manner as in Example 1, except that in preparing the coating liquid for the release layer in Example 1, 42.8 parts of stearyl phosphate potassium salt (product name: U-Pol 1800, manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., solid content concentration 35%) was replaced with 75 parts of a long-chain alkyl group-containing resin (product name: Resem T-738, manufactured by Chukyo Yushi Co., Ltd., solid content concentration 20%), and the amount of water was changed from 58.3 parts to 26.1 parts.

[0092] Comparative Example 4 A pseudo-adhesive label was obtained in the same manner as in Example 1, except that in preparing the coating liquid for the release layer in Example 1, 42.8 parts of stearyl phosphate potassium salt (product name: U-Pol 1800, manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., solids concentration 35%) was replaced with 50 parts of silicone acrylic resin (product name: Chaline FE-230N, manufactured by Nissin Chemical Industry Co., Ltd., solids concentration 30%), and the amount of water was changed from 58.3 parts to 51.1 parts.

[0093] The pseudo-adhesive labels produced in the above Examples 1 to 7 and Comparative Examples 1 to 4 were subjected to the following evaluations. The results are shown in Table 1.

[0094] [Evaluation of peelability] The pseudo-adhesive label was cut into a test piece of 5cm x 10cm, the release substrate was peeled off and the piece was attached to a paperboard, and the test piece was then conditioned for 5 hours at 23°C and 50% RH. The peel strength of the pseudo-adhesive interface was measured, and the peeling sensation when peeled by hand was evaluated. The peel strength was measured using a high-speed peeling ZPE-1100W made by IMASS, and the test piece was peeled at 180 degrees at a peeling speed of 10m / min. The criteria for the sensory evaluation of the peeling sensation were as follows: ○: Peeling from the pseudo-adhesive interface was possible with light force. △: Peeling was heavy, but peeling from the pseudo-adhesive interface was possible. ×: The adhesive could not be peeled cleanly from the pseudo-adhesive interface, and the adhesive peeled off from the paperboard, or the paper layer of the substrate was destroyed.

[0095] [Cardboard peelability] The pseudo-adhesive label was cut into a test piece of 5cm x 10cm, the release substrate was peeled off, and the piece was attached to a cardboard surface. After one hour in an environment of 23°C and 50% RH, the state of the release surface was evaluated by hand. The criteria for the sensory evaluation of the state of the release surface were as follows: ○: Peeling is possible from the pseudo-adhesive interface. Δ: Generally peelable from the pseudo-adhesive interface, but some areas of the pseudo-adhesive layer and the adhesive layer were observed to be taken up by the slip side. ×: The adhesive could not be peeled cleanly from the pseudo-adhesive interface, and the adhesive peeled off from the cardboard surface, or the paper layer of the base material was destroyed.

[0096] [Water resistance of pseudo-adhesive layer] To evaluate peelability, after peeling off the slip, a drop of water was placed on the pseudo-adhesive layer remaining on the paperboard side, and then a piece of wood-free paper was placed on top of it and left to dry naturally for a day. The wood-free paper was then peeled off and the presence or absence of blocking was confirmed. Water resistance was evaluated according to the following criteria: ◯: No blocking occurred and the wood-free paper was peeled off without resistance. Δ: There were some areas where the paper was slightly stuck, and there was some resistance when peeling off the fine paper. ×: There was sticking, there was a large resistance when peeling off the high-quality paper, and the high-quality paper was torn.

[0097] [Table 1]

Claims

1. A pseudo-adhesive laminate having a release layer and a pseudo-adhesive layer, in that order, on one side of a support, wherein the support and the pseudo-adhesive layer are peelable, and wherein the release layer contains an alkyl phosphate ester having an alkyl group having 12 or more carbon atoms.

2. 10. The pseudo-adhesive laminate of claim 1, wherein said alkyl phosphate is a stearyl phosphate.

3. The pseudo-adhesive layer contains polyvinyl alcohol and / or modified polyvinyl alcohol in an amount of 20% by mass or more based on the total solid content, and the coating amount of the pseudo-adhesive layer after drying is 2 to 8 g / m 2 2. The pseudo-adhesive laminate of claim 1 , wherein:

4. 4. The pseudo-adhesive laminate of claim 3, wherein either or both of the release layer and the pseudo-adhesive layer contain a crosslinking agent.

5. The pseudo-adhesive laminate according to any one of claims 1 to 4, further comprising an adhesive layer and a release substrate in this order on the pseudo-adhesive layer opposite the release layer.

Citation Information

Patent Citations

  • Nonadhesive invoice label and manufacturing method thereof

    JP2016175410A

  • Pseudo adhesion laminate

    JP2019147316A

  • Pseudo adhesion laminate

    JP2019147317A

  • Pseudo adhesion laminate

    JP2019147898A

  • Peelable laminate

    JP2020163840A